Effect of deforestation and subsequent land-use management on soil carbon stocks in the South American Chaco - Osinaga, Natalia Andrea (2018)
The sub-humid Chaco region of Argentina, originally covered by dry sclerophyll forest, has been subjected to clearing since the end of the ´70 and replacement of the forest by no till farming. Land use changes produced a decrease in aboveground carbon stored in forests, but little is known about the impact on soil organic C stocks. The aim of this study was to evaluate soil C stocks and C fractions up to 1 m depth in soils under different land use: < 10 yr continuous cropping; > 20 yr continuous cropping, warm season grass pasture and native forest in 32 sites distributed over the Chaco region. The organic C stock content up to 1 m depth expressed as equivalent mass varied as follows: forest (119.3 Mg ha−1) > pasture (87.9 Mg ha−1) > continuous cropping (71.9 and 77.3 Mg ha−1), with no impact of the number of years under cropping. The most sensitive organic carbon fraction was the coarse particle fraction (2000 μm?212 μm) at 0?5 cm and 5?20 cm depth layers. Resistant carbon (< 53 μm) was the main organic matter fraction in all sample categories except in the forest. Organic C stock, its quality and distribution in the profile were sensitive to land use change. The conversion of the Chaco forest to crops was associated to a decrease of Organic C stock up to the meter depth and with the decrease of the labile fraction. The incorporation of pastures of warm-season grasses was able to mitigate the decrease of C stocks caused by cropping and so could be considered a sustainable management practice. As soil organic carbon losses were not restricted to the first few cm of the soil, the development of models that would allow the estimation of soil organic carbon changes in depth would be useful to evaluate with greater precision the impact of land use change on carbon stocks.